2018
DOI: 10.1002/ece3.4628
|View full text |Cite
|
Sign up to set email alerts
|

No support for cryptic choice by ovarian fluid in an external fertilizer

Abstract: Whether the ovarian fluid (OF) represents a selective environment influencing cryptic female choice was tested using an external fertilizer experiencing intense sperm competition and large effects of OF on sperm swimming behavior—the Arctic charr (Salvelinus alpinus). We physically separated the OF from the eggs of reproductively active females and reintroduced either their own OF or fluid from another female to the eggs. The eggs were then fertilized in vitro in a replicated split‐brood design with sperm from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Although many of these studies implicate FRF as a critical moderator of sperm competition, not all of them have revealed consistent effects. For example, studies of the quacking frog (Crinia georgiana) [46], lake trout (Salvelinus namaycush) [58], arctic charr [59] and capelin (Mallotus villosus) [60] reported no evidence for male-by-female interaction effects moderated by the FRF. Similarly, in the ant (Acromyrmex echinatior), there is no evidence of FRF-mediated inbreeding avoidance [26].…”
Section: (B) Differential Effects Of Female Reproductive Fluid On Spementioning
confidence: 99%
“…Although many of these studies implicate FRF as a critical moderator of sperm competition, not all of them have revealed consistent effects. For example, studies of the quacking frog (Crinia georgiana) [46], lake trout (Salvelinus namaycush) [58], arctic charr [59] and capelin (Mallotus villosus) [60] reported no evidence for male-by-female interaction effects moderated by the FRF. Similarly, in the ant (Acromyrmex echinatior), there is no evidence of FRF-mediated inbreeding avoidance [26].…”
Section: (B) Differential Effects Of Female Reproductive Fluid On Spementioning
confidence: 99%
“…On the other hand, studies have also demonstrated that OF can have a limited or negative impact on spermatozoa performance [13,51,52]. For instance, in rainbow trout, OF from particular females inhibited spermatozoa motility, while other OF samples initiated motility and dissimilarly affected spermatozoa performance [13,52].…”
Section: Ovarian Fluid Impacts On Spermatozoamentioning
confidence: 99%
“…, can be modified by female reproductive fluids (Yeates et al, 2013;Holt & Fazeli, 2015;Alonzo et al, 2016;Rosengrave et al, 2016;Lymbery et al, 2017; but see Kleppe et al, 2018)). For example, in broadcast spawners, such as the mussel (Mytilus galloprovincialis), sperm chemotaxis via exposure to 'egg water' differentially affects sperm velocity and patterns of motility depending on the combinatorial identities of the male and females contributing to the interaction (Lymbery et al, 2017).…”
mentioning
confidence: 99%